IN SILICO DOCKING STUDY OF HERBAL COMPOSITION AND DEVELOPMENT OF MOUTH DISSOLVING TABLETS FOR COMMON RESPIRATORY DISEASES THEREOF - CHANDWANI, ANKITA; MODI, KARUNA; SHAH, KAUSHIK; SHAH, MAMTA (International Journal of Current Pharmaceutical Research, 2024)
Objective: The present study aims to develop a novel mouth dissolving tablets containing a combination of herbal extracts and a bioactive constituent and evaluating it for activity against common respiratory diseases (in silico studies). Methods: Docking study was done to provide a scientific foundation, keeping the traditional knowledge as a base. Four trial batches were developed. The final batch was then formulated and various pre and post-compression and assays were performed to evaluate the formation of good quality of product. The final batch was prepared by the method of direct compression and taken for accelerated stability studies. Results: The final batch containing 10 % active ingredients, 7.5 % super-disintegrant and 47 % diluent was found to be stable, easily producible and economic. Conclusion: This research work grasps possibilities for researchers in the development and evaluation of mouth-dissolving tablets with significant bioactive potential against common respiratory diseases.